(untitled) (Zaporizhzhia Historical Review, 2021)
Recently considerable changes have taken place in our country (political, economical), which reguire changes of political authority. This process has confident peculiarities in Ukraine. Fundamental chanqes have not taken place. Former administration beqan forminq the authority of state orqans.